IDENTIFIKASI STRUKTUR DAN FUNGSI TANAMAN SEBAGAI PEREDAM KEBISINGAN DI MEDIAN JALAN KOTA PEKANBARU - Gulo, Lamsari Efrida; Sulaeman, Rudianda; Yoza, Defri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Road is a visual axis that is straight, strong, and directing our view like a straight line. In 2014 the volume of vehicles on the jalanJenderal Sudirman in Pekanbaru is 163.296 units per day. The arterial road (urban) shows that the indications of the noise level is quite high. Greening the city is one of the ways in reducing noise. This researchÂ aimed to compare the types and the structures of plants in the median of jalanJenderalSudirman as the noise reducer. This research was conducted by dividing jalan JenderalS udirman in Pekanbaru city into seven zones of observation. Each zone made measuring 20 X 20 m that were determined randomly. The choice of the plants in each indentified zone should represent the existing plants structure along the observation zone. The phase of identifying the structure of the plant in include the measurement of the tree diameter, the tree heigt, the tree canopy, the tree damage and the noise level. Woody plants and ground plants, which have the lowest noise structure, have the lowest noise intensity compared with woody plants and ground plants which have the single structure. Keywords :Road, Noise, Plants